2018
DOI: 10.31234/osf.io/yb4z2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconsidering the roots, structure, and implications of gambling motives: An integrative approach

Abstract: Accurately identifying motives is crucial in the functional analysis of gambling behavior. In this study, a data-driven approach was followed to clarify the factor structure underlying a pool of motives for gambling, selected from the Gambling Motives Questionnaire – Financial (GMQ-F), and the Reasons for Gambling Questionnaire (RGQ), in a sample of regular problem and non-problem gamblers. Additionally, the role of gambling motives in the relationship between root behavioral activation/inhibition systems (BIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The results also showed that gambling type was significantly associated with specific coping motives, suggesting that mixed gambling and coping motives are closely linked. This result is not surprising, as previous studies have highlighted that gamblers who play to escape or reduce negative affect usually move to games of luck where no reflection is required [ 10 , 31 , 36 , 54 ]. Moreover, the association between coping motives and problematic gambling is one of the most solid results in gambling research.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The results also showed that gambling type was significantly associated with specific coping motives, suggesting that mixed gambling and coping motives are closely linked. This result is not surprising, as previous studies have highlighted that gamblers who play to escape or reduce negative affect usually move to games of luck where no reflection is required [ 10 , 31 , 36 , 54 ]. Moreover, the association between coping motives and problematic gambling is one of the most solid results in gambling research.…”
Section: Discussionmentioning
confidence: 53%
“…On the one hand, the financial motive cannot be dissociated from this type of game, and on the other hand can lead to losses that can be fueled by cognitive distortions such as the illusion of control [ 15 ]. The recent integrative study of Barrada and colleagues [ 10 ], aiming to clarify the factor structure underlying a pool of motives for gambling from two widely used gambling motivation assessment tools (the Gambling Motives Questionnaire–Financial [GMQ-F], and the Reasons for Gambling Questionnaire [RGQ), also identified the first three factors (social, financial, fun-/thrill-related) and grouped positive and negative reinforcement as a fourth one (affect regulation factor).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations